Bright white light emission from blue emitting carbon dot-coated Dy3+- doped luminescent glasses - Ozlem, Beyza; Korkmaz, Ulai; Erol, Erdinc; Alai, Melis Ozge; Meray, Zeynep; Alturk, Rukan Genc; Ersundu, Miray Celikbilek; Ersundu, Ali Ercin (ELSEVIER SCIENCE SA, 2022)
Dy3+-doped luminescent glasses have received great attention due to their ability to emit white light at a suitable yellow-to-blue intensity ratio. However, achieving bright white light using single Dy3+-doped glasses remains a challenge due to the hypersensitivity of the emission band at 575 nm - usually resulting in intense yellow emission. In this work, we present a novel approach for compensating for the blue emission deficiency of Dy3+ to produce resin-free white light-emitting diodes (WLEDs) by synthesizing two series of Dy3+-doped glasses from tellurite and silicate systems on which blue-emitting carbon dots (BCDs) are spin-coated. The structural, chemical, optical, and luminescence properties of tellurite and silicate glasses are compared and discussed in detail. White light emissions are obtained upon 365-nm excitation for BCD-coated Dy3+-doped tellurite and silicate glasses with color coordinates of (x = 0.31, y = 0.33) and (x = 0.31, y = 0.34) and correlated color temperatures (CCT) of 5518 K and 5316 K, respectively. BCDs coating increases photoluminescence quantum yield (PLQY) values from 3.10 % to 5.62 % and from 20.81 % to 31.49 % for tellurite and silicate glasses, respectively. Ultimately, the findings in this work show the potential of BCD-coated luminescent glasses with excellent luminescent properties to be considered in solid-state lighting applications. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: Luminescent glass; Dy3+; Tellurite; Silicate; Carbon dots; White light; SILICATE GLASS; LASER; EU3+; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering